A survival guide to multi-level marketing in Singapore. - Cheok, Ling. (2008)
This project attempts to find out why MLM is increasingly popular in Singapore; what are the unique characteristics of products suitable for distribution through MLM and finally a guideline for operating an MLM company in Singapore is proposed.